NATURE’S REMEDY: PLANT-BASED THERAPIES FOR DIABETIC ALZHEIMER’S - Sayyada Saleha Momina; Kumaraswamy Gandla (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Type 2 diabetes and Alzheimer’s disease, when both conditions occur simultaneously, greatly worsen neurodegeneration and cognitive decline, making diabetic Alzheimer’s disease a difficult healthcare issue to solve. Medicine derived from plants is gaining attention as a potential new treatment option due to its abundance of bioactive chemicals that have anti-diabetic and neuroprotective effects. This analysis focuses on the many ways in which chemicals found in plants have the potential to treat Alzheimer’s disease in people with diabetes. Many chemicals found in plants have the potential to influence key pathways that are involved in the development of diabetes and Alzheimer’s disease. Insulin signalling pathways, neuroinflammation, and amyloid-beta metabolism are all part of this category. Experts in the field may discover new ways to help diabetics slow down cognitive loss and neurodegeneration by using the wide variety of bioactive substances found in plants.